Wastewater treatment for nutrient removal with Ecuadorian native microalgae - Benítez, María Belén (Environmental technology, 2019)
The aim of this project was to study the feasibility of utilizing native microalgae for the removal of nitrogen and phosphorus, as a potential secondary wastewater treatment process in Ecuador. Agitation and aeration batch experiments were conducted using synthetic secondary wastewater effluent, to determine nitrogen and phosphorus removal efficiencies by a native Ecuadorian microalgal strain. Experimental results indicated that microalgal cultures could successfully remove nitrogen and phosphorus. NH4+-N and PO43--P removal efficiencies of 52.6 and 55.6%, and 67.0 and 20.4%, as well as NO3--N production efficiencies of 87.0 and 93.1% were reported in agitation and aeration photobioreactors, respectively. Aeration was not found to increase the nutrient removal efficiency of NH4+-N . Moreover, in the case of PO43--P , a negative impact was observed, where removal efficiencies decreased by a factor of 3.3 at higher aeration rates. To the best of our knowledge, this is the first report of the removal of nutrients by native Ecuadorian Chlorella sp., hence the results of this study would indicate that this native microalgal strain could be successfully incorporated in a potential treatment process for nutrient removal in Ecuador